2021
DOI: 10.3389/fphar.2021.739658
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin Induces Apoptosis and Inhibits Metastasis of Breast Cancer Cells via Regulating RXRα-AKT Signaling Pathway

Abstract: Mangostin, which has the function of anti-inflammatory, antioxidant, and anticancer, etc, is one of the main active ingredients of the hull of the mangosteen. The main objective of the study was to elucidate its anti-cancer function and possible mechanism. α-Mangostin was separated and structurally confirmed. MTT method was used to check the effect of mangostin on breast cancer cell proliferation. Then the effect of α-Mangostin on the transcriptional activity of RXRα was tested by dual-luciferase reporter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Moreover, our results agree with the results of Lee et al, (2017), who demonstrate that α‐M induces apoptosis through the activation of ROS and caspase 3 cleavage in cervical cancer cells. Also, our results agree with Zhu et al (2021) results, who demonstrate that in MDA‐MB‐231, a TNBC cancer cell model, α‐M induced apoptosis and avoided proliferation and migration by activating PI3K/Akt signaling pathway. α‐M also promoted BAX activation along with caspase 3 cleavage, which was demonstrated in MCF‐7, a breast cancer cell line that expresses the ER, where α‐M induced the overexpression of modulator of apoptosis 1, causing the activation of BAX and caspase 3 and later triggering apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, our results agree with the results of Lee et al, (2017), who demonstrate that α‐M induces apoptosis through the activation of ROS and caspase 3 cleavage in cervical cancer cells. Also, our results agree with Zhu et al (2021) results, who demonstrate that in MDA‐MB‐231, a TNBC cancer cell model, α‐M induced apoptosis and avoided proliferation and migration by activating PI3K/Akt signaling pathway. α‐M also promoted BAX activation along with caspase 3 cleavage, which was demonstrated in MCF‐7, a breast cancer cell line that expresses the ER, where α‐M induced the overexpression of modulator of apoptosis 1, causing the activation of BAX and caspase 3 and later triggering apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the latter, chemotherapy is the only available therapy for TNBC, which could induce side effects and chemoresistance. α‐M has shown anticancer effects in different cancer models (Lee et al, 2016; Zhu et al, 2021), so this polyphenol could be a potential therapy for the treatment of TNBC. For example, Perez‐Rojas et al (2016) showed that α‐M induces apoptosis in a cervical cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…α-mangostin (α-MG) is a representative natural xanthone isolated from the pericarps of mangosteen. It has been proven to possess a variety of pharmacological properties, such as anticarcinogenic, anti-inflammatory, antidiabetic, and antioxidant activities ( 13 , 14 ), as well as hepatoprotective, cardioprotective, and neuroprotective properties. Of these, its anticarcinogenic activity is the most promising ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another research reported that α-mangostin suppressed the proliferation, migration, and invasion of the PI3K/Akt signaling pathway by targeting RXRα and cyclin D1 in vitro and in silico studies. This compound was inhibited in the MDA-MB-231 cell line, with an IC 50 value of 11.37 µM [165].…”
Section: α-Mangostinmentioning
confidence: 99%